Penerapan Metode Kontekstual Inkuiri Dalam Pembelajaran Pendidikan Agama Islam - Agus Budiman; M. Munfarid (Educan : Jurnal Pendidikan Islam, 2017)
Learning concept known as a “Contextual Teaching and Learning” is a learning which include an “experience” philosophy and “experience” learning concept, which will make learning atmosphere more exciting and pleasure. The aim of this research is to observe the implementation of Inquiry Contextual Method in Islamic learning and to know what the implementation problems are. This research is a qualitative research. In submitting the data, researchers use three different methods. The first is interview method, and the second is observation method, and the last is documentation. Writer utilizes three methods also to analyze data. Those are data collection, data reduction, data presentation and conclusion. This research outcome indicate that the implementation of Inquiry Contextual method in Islamic learning in the first PGRI vocational high School in Ponorogo. Before teaching activity, teacher creates such as topic problem formulas, standard competency and basic competency formula, decide a learning media, and explaining a method scenario. In practice, teacher explains basic ability which will be achieved by student. Afterwards, student will divide in four different clusters, which each cluster include ten students than given with different matter. Students acquire learning references such as LKS and many books that provided by the teacher.